2021
DOI: 10.1111/jems.12441
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal stability of survey‐based measures of risk and time preferences

Abstract: Given the importance of risk and time preferences for economics and other disciplines, we seek to examine the intertemporal stability of six related survey-based measures. Using a panel of subjects over three waves, between 2013 and 2015, we find remarkably high aggregate stability over the examined period in all six measures while we observe significant patterns of instability at the individual level. Our results contribute to the discussion on the wider adoption of survey-based measures, especially consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Another aspect is the temporal stability of the three measures: The subjects' decisions differ substantially when they repeat the tasks after a certain time. Researchers have found that risk attitudes elicited by the SOEP risk questions are stable over different time horizons (intervals up to 10 years) (Drichoutis & Vassilopoulos, 2021; Galizzi & Miniaci, 2016; Lönnqvist et al, 2015; Mata et al, 2018). A rather poor temporal stability is found for the HL task and the IG.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another aspect is the temporal stability of the three measures: The subjects' decisions differ substantially when they repeat the tasks after a certain time. Researchers have found that risk attitudes elicited by the SOEP risk questions are stable over different time horizons (intervals up to 10 years) (Drichoutis & Vassilopoulos, 2021; Galizzi & Miniaci, 2016; Lönnqvist et al, 2015; Mata et al, 2018). A rather poor temporal stability is found for the HL task and the IG.…”
Section: Literature Reviewmentioning
confidence: 99%